Most favoured nation principle and national treatment obligation and their efficacy in elimination of the discrimination - Dr. Ikram Ullah (Al Manhal Research Journal, 2022)
In international trade, the non-discriminatory treatment by exporting countries to the products and services being imported from other countries is a matter of utmost significance. To this end WTO regime puts in place two principles i.e. most favoured nation principle and national treatment obligation. They have proved very effective to achieve the purpose for which they were enacted. In addition to the content of these provisions, the interpretations rendered over them also accumulated the benefit. This paper explains these obligations in the light of Panel Reports, Appellate Body Reports and Working Party Reports and demonstrates that they have effectively eradicated the discrimination in these subjects.